PSVII-13 The Effects of In Ovo Injection of Nicotinamide Riboside on Avian Myogenesis. (7th December 2018) - Davis, S; Khatri, O; Phelps, K; Gonzalez, J
Abstract: The objective of this study was to determine the effects of in ovo injection of nicotinamide riboside (NR) on avian embryonic myogenesis. At 10-days of incubation, 156 fertilized broiler eggs (Cobb 500) were randomly assigned to 1 of 4 treatments of a completely randomized design with a 2 × 2 factorial arrangement. Factor 1 was treatment (TRT), with eggs injected with 100 µl of 0.0 (NRNeg) or 2.5 mM (NRPos) NR in sterile saline. Factor 2 consisted of injection location (LOC), with treatments injected into the yolk or albumin. Eggs were incubated at 37 ± 3°C throughout incubation, while relative humidity was set to 40 ± 2% for the first 18 days and increased to 60 ± 2% for the final 3 incubation days. Twenty-four hours after hatching, chicks were euthanized by prolonged exposure to CO2 and decapitation. Measurements including chick weight and left Pectoralis major (PM) weight, length, width and depth were collected. There were no TRT×LOC interactions for all measures (P >0.07) exceptPM weight and length (P. When injected in the yolk, NRPos chicks' PM muscles were heavier (P>0.01) than NRNeg chicks; however, there was no difference (P=0.08) in weight when treatments were injected in the albumin. The PM was longer (P=0.05) in NRPos chicks compared to NRNeg when treatments were injected in the albumin, but a greater difference (P>0.01) was found when NR was injected into the yolk. Chick weight was not affected by TRT or LOC (P>0.17) and LOC did not affect PM width or thickness (P>0.09). Treatment affected PM width and depth (P>0.01), with NRPos chicks having wider and thicker muscles that NRNeg chicks. Injecting NR into the egg of the developing broiler embryo increases PM muscle development and data would indicate greater positive effects when NR is injected into the yolk.